Daya Gabung Umum, Daya Gabung Khusus dan Keragaan Hasil Hibrida Jagung pada Dua Tingkat Pumupukan N - Sutoro, Sutoro; Setyowati, Mamik (Jurnal Penelitian Pertanian Tanaman Pangan, 2015)
Maize grain production may be increased by growing varieties that utilize the available nutrients in the soil efficiently. High grain yield of maize could be achieved when hybrid variety was planted under the optimal rate of fertilization. However, application of fertilizer on agricultural land in large quantities have a negative impact on the environment. Therefore, maize variety that is able to use fertilizer efficiently is needed, which would be reducing the environmental impact from a high fertilization and also helping farmers who are less able to provide optimal fertilizer rate or those who are growing maize under the marginal land. Maize genotypes developed by diallel mating and their parents were tested under nested design, three replications on two levels of nitrogen fertilization (low and optimal N level, as nested factor). The full diallel crosses (hybrids and reciprocals) derived from five inbred lines were tested using Griffing method I. Result indicated that H3, H7 and H9 hybrids were adaptable to low N. Inbred G2 and G5 were suitable for optimal N fertilization condition, and their single cross hybrids using H7 as parent was suitable for the low N fertilization condition. Inbred G4 was suitable for low N condition and inbred G5 was suitable for the optimal N condition. Single cross hybrids of H10 was as parent suitable for N optimal condition. It was shown that maize hybrids suitable for low or optimal N fertilizations could be generated from either pairs of inbreds adaptif under low N or optimal N conditions. Inbred lines adapted to certain N fertilization may not necessarily produced hybrid adapted to the same N level of environment.